Dynamic 320‐slice CT larynx for detection and management of idiopathic bilateral vocal cord paralysis. Issue 1 (20th December 2013) - Ruane, Laurence E.; Lau, Kenneth K.; Low, Kathy; Crossett, Marcus; Vallance, Neil; Bardin, Philip G.
Abstract Idiopathic bilateral vocal cord paralysis (VCP) is a rare and difficult condition often undiagnosed and frequently confused with asthma and other respiratory conditions. Accurate diagnosis is crucial since 80% of cases patients require surgical intervention, such as tracheostomy or laser surgery, to relieve symptoms. The "gold standard" for diagnosing VCP has been laryngoscopy. In this case study, we demonstrate for the first time that idiopathic bilateral VCP can be accurately diagnosed by means of a novel noninvasive methodology: dynamic volume 320‐slice computed tomography larynx. Three‐dimensional reconstruction of laryngeal motion during the breathing cycle permitted functional assessment of the larynx showing absence of vocal cord movements. The new methodology may be valuable for noninvasive diagnosis of vocal cord movement disorders before and for follow‐up after surgery.